PEMANFAATAN PLATFORM RAPOR PENDIDIKAN INDONESIA TERHADAP PERENCANAAN BERBASIS DATA - Musakirawati , Musakirawati; Jemmy, Jemmy; Anggriawan, Ferry; Triansyah , Fadli Agus; Akib, Akib; Tahir, Abdul (Universitas Negeri Surabaya, 2023)
The Ministry of Education, Culture, Research, and Technology (Kemdikbudristek) issued an Independent Learning policy in order to achieve quality education for all Indonesian people. Quality education focuses on developing basic competencies and character to ensure students progress in learning so that they are more competent and have character. One of the Independent Learning policies that have been launched is the Educational Report platform. The Educational Report Platform that was launched, is a platform that provides data on reports on the results of the evaluation of the education system as an improvement on previous quality report platform. This research is a descriptive qualitative study to examine how the newly launched Indonesian Educational Report platform can be utilized in data-based education planning so that the planning carried out can be more targeted and the quality of education can be improved. The results of the study have shown that the use of Educational Report in data-based planning is a tool and a way to identify root causes, reflect on educational achievements, and become a material for constructive discussions with various education stakeholders to improve the quality of education.